Determinan Minat Investasi Saham Pada Mahasiswa - Rona, I Wayan; Sinarwati, Ni Kadek; Suci, Ni Made (Universitas Prasetiya Mulya, 2023)
This study aims to analyze the effect of overconfidence, herding, cognitive dissonance, and the illusion of control bias on the intention to invest in stocks. The subjects of this study are students who are members of an established investment gallery membership in some Universities located in Bali with an age range of 18-26 years. The objects of this research consist of overconfidence, herding, cognitive dissonance, and the illusion of control as the independent variables, and intention to invest in stock as the dependent variable. The numberof samples in this study was 118 people. The data collection technique uses the questionnaire filled out through Google Forms media. The data analysis technique uses inferential statistical analysis techniques using a multiple linear regression model and the SPSS application (statistical product and service solution) as a data processing media. The results showed: (1) Overconfidence significantly positively affects the intention to invest in stock. (2) Herding, Cognitive dissonance, and Illusion of control have no significant effect on the intention to invest in stock.